ENTREPRENEURSHIP AND NATIONAL DEVELOPMENT : A PROPOSAL FOR EVANGELISTIC AGENDA - O.J.K Ogundele; James O. Abiola (European Scientific Journal, ESJ, 2012)
The paper considers all the process of ministering the entrepreneurial personality, right from childhood to the time of retirement from active entrepreneurial practice, if ever possible, as development. It also specifies development as a construct used to explain economic expansion. It posits an agenda of developing the entrepreneur from cradle to the grace which involves active participation of virtually all forms of institutions in the society; the models to be used as vehicle for evangelistic entrepreneurial development are presented. The paper contends that the era of relying on natural entrepreneurs for economic development, based on the experience from south East Asia is gone. Therefore, if we hope to have great and dynamic economy, we must develop indigenous entrepreneurs by equipping them with necessary capacity to face the challenges of the 21st century. This calls for active involvement of all economic, social, political, technical institutions and offices. It also demands the development of multiple skills in our entrepreneurs. Twenty eight of such skills are outlined for future trainers of indigenous entrepreneurs in Nigeria.